Clinical Profile and Management of Neovascular Glaucoma in North India - Ketaki Rajurkar; Suneeta Dubey; Monica Gandhi; Prachi Gurav; Julie Pegu (Delhi Journal of Ophthalmology)
Purpose: To report the etiology, clinical features, treatment and outcomes of neovascular glaucoma (NVG) in a tertiary care ophthalmic center. Background: NVG is a devastating ocular disease often leading to loss of vision. The current standard of care includes retinal phtocoagulation and control of increased intraocular pressure with medical and surgical therapy like trabeculectomy, Ahmed Glaucoma Valve (AGV) and Trans scleral cyclophotocoagulation (TSCPC) with studies comparing them showing varied results. We compared these treatment modalities to find out which is better for IOP control. Methods: Retrospective file review. Results: 230 eyes of 217 patients with NVG were studied. Mean age of the population was 56.99 ± 13.8 years. Venous occlusion (37.4%) was the commonest cause of NVG followed by diabetic retinopathy (35.2%). All the patients were managed medically to begin with. Ninety one patients underwent surgical management. Pan retinal photocoagulation was done for 68.75% patients. Anti- vascular endothelial growth factor (VEGF) was given intravitreally for 56.25% patients prior to surgery. Thirty six patients underwent trabeculectomy with Mitomycin C (MMC), eleven patients underwent AGV implantation and thirty three underwent TSCPC. Best corrected visual acuity at baseline was 2.24 ± 0.99. Final visual acuity was 2.67 ± 1.1. Best corrected visual acuity (BCVA) was either stable or improved from baseline in 46.25% patients and deteriorated in 53.5%. All three modalities were equally effective in reducing IOP from baseline (p = 0.00) and there was no statistically significant difference between them taking IOP into consideration as success criteria (p = 0.60). Hyphaema was the commonest complication (22.5%). Conclusion: Venous occlusion was the commonest cause of NVG in our setup. All three modalities of treatment, AGV, trabeculectomy with MMC and TSCPC are effective in controlling the disease process. The visual prognosis however remains poor despite surgical treatment due to late presentation and fast progression.